Palliative care in policy documents for adults with cancer and non-cancer diseases with potential palliative care needs: a document analysis - Anna O’Sullivan; Linnéa Carling; Joakim Öhlén; Stina Nyblom; Anneli Ozanne; Ragnhild Hedman; Carl-Johan Fürst; Cecilia Larsdotter (Palliative Care and Social Practice)
Background: The inclusion of palliative care in policy has been encouraged internationally, and gradually implemented, including in Sweden. Care should be driven by policy; hence, examining how palliative care is included in national policy documents is paramount. Objectives: This study aimed to examine how palliative care is included in national disease-specific policy documents for adults with chronic conditions, cancer and non-cancer, with potential palliative care needs. Design: Document analysis. Methods: A document analysis of Swedish policy documents for different disease-specific groups with severe chronic conditions, cancer and non-cancer, was performed. In total, 96 documents were analysed. Results: How palliative care was included in the policy documents varied from mentioning the term without explanation to detailed discussion regarding palliative care practice. Such discussion encompassed several conceptualisations of palliative care: defined through authorities’ definitions; as care of dying persons; integrated with disease-specific care and treatment; limited to disease-specific medical treatments or based on detail regarding certain key elements of palliative care such as specialised palliative care and end-of-life conversations. Conclusion: There may be large variations in how palliative care is conceptualised in national disease-specific policy documents, as disclosed by this analysis of the Swedish case. Limiting palliative care to disease-specific medical treatments (most commonly palliative oncological treatments) or the care of dying persons limits its scope in ways contrary to current evidence supporting early integrated palliative care. The lack of palliative care recommendations adapted for each specific diagnosis indicates a gap in policy. To promote equal access to palliative care regardless of patients’ diseases or medical conditions, the importance of how palliative care is included in national policy documents needs to be further acknowledged and discussed – with palliative care consistently included in such documents.